2012
DOI: 10.3109/00207454.2012.746334
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Epileptiform Discharges and the Sleep Cycle in 200 Epileptic Patients

Abstract: Combination of long-term video EEG with polysomnography is a useful method to analyze associations between EDs and the sleep-wake cycle. This strategy can also help identify the nature of sleep disorders in epileptic patients, which may improve the treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Markers of sleep fragmentation were higher than the control group, indicating an increase in the number of stage shifts, number of arousals and number of arousal indices in NREM and REM sleep (Table 2). Our data were consistent with previous reports on sleep fragmentation in patients with TLE [32,46,47].Yu-Dan et al (2013) previously showed that there was an association between epileptic form discharges and the sleep cycle in 200 patients with epilepsy [48]. This association was particularly higher in cases of temporal lobe epilepsy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Markers of sleep fragmentation were higher than the control group, indicating an increase in the number of stage shifts, number of arousals and number of arousal indices in NREM and REM sleep (Table 2). Our data were consistent with previous reports on sleep fragmentation in patients with TLE [32,46,47].Yu-Dan et al (2013) previously showed that there was an association between epileptic form discharges and the sleep cycle in 200 patients with epilepsy [48]. This association was particularly higher in cases of temporal lobe epilepsy.…”
Section: Discussionsupporting
confidence: 93%
“…This association was particularly higher in cases of temporal lobe epilepsy. In addition, these patients demonstrated longer mean sleep time during lighter sleep stages [48]. This data might explain the cognitive dysfunction and daytime symptoms observed in some patient cases, even though the seizures were under control.…”
Section: Discussionmentioning
confidence: 74%
“…First identified in the 1930s, IEDs are regarded as a hallmark of epilepsy and while researchers remain uncertain as to their significance they are widely believed to reflect cortical hyperexcitability. The frequency of IEDs increases after sleep deprivation and is higher during NREM sleep which also has the highest tendency for seizures during the sleep cycle [305][306][307][308][309][310][311]. Such heightened susceptibility, once again, is attributable to diminished amplitude of the electromagnetic wave function.…”
Section: Threshold and Susceptibilitymentioning
confidence: 99%
“…Sleep spindles are an electrographic signature of sleep that correlate in frequency with interictal spike-wave discharges ( 25 ) and may be biomarkers of epilepsy in humans ( 26 ). They are relevant in both generalized ( 27 ) as well as focal epilepsy ( 28 ) and display altered morphology in many epilepsy patients ( 29 ). Sleep spindles are also subject to regulation by circadian rhythms ( 30 ).…”
Section: Time Of Day and Sleep/wake Effects On Seizures In Epilepsymentioning
confidence: 99%